Length-weight relationship and growth pattern inference of a small indigenous freshwater Prawn, Macrobrachium lamarrei (H. Milne-Edwards, 1837) in Bangladesh - Ara, Motia Gulshan; Nabi, Md Noor; Ahmed, Zoarder Faruque; Fatema, Mst Kaniz (Research in Agriculture Livestock and Fisheries, 2015)
The length-weight relationships (LWRs) of Macrobrachium lamarrei (H. Milne-Edwards, 1837) was studied to construct the generalized relationships of body weight to carapace length measurements for male, female and combined prawn population separately over a calendar year. A total of 1018 specimens were used for this study. The parameter values of the equation W = a Lb describing the relationships between body weight and carapace length for male, female and combined prawns. The parameter of equations, a varied from 0.00096 to 0.00333, 0.00059 to 0.00728 and 0.00081 to 0.00440 for male, female and combined prawn population respectively. On the other hand, the slope of equations, b varied from 2.4363 to 2.8229, 2.0761 to 3.0314 and 2.2915 to 2.8998 for male, female and combined prawn population respectively indicating isometric growth in females but negative allometric for males suggesting that female prawns were comparatively in better condition than males of the same population. The generalized length-weight relationship was fitted with the pooled data of all monthly samples for male, female and combined prawn separately which were BW = 0.0008 CL2.924, BW = 0.0012 CL2.783 and BW = 0.0010CL2.845 respectively indicating negative allometric growth as b varied from 2.783 to 2.924. The results further revealed that all length-weight relationships (LWRs) were highly correlated (r2 > 0.904). DOI: http://dx.doi.org/10.3329/ralf.v1i1.22377 Res. Agric., Livest. Fish.1(1): 137-145, Dec 2014